Ulus Jochi in system of international trade on territory of Crimean Peninsula in XIII–XIV centuries - E. A. Koshechkina (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the analysis of the foreign economic policy of the ulus of Jochi in the XIII-XIV centuries. The role of the Ulus in the system of international trade on the territory of the Crimean Peninsula is considered. The analysis of foreign economic policy directions and their role in the economy Of ulus Juchi in the declared period is carried out. The importance of international trade in the economy of the Golden Horde is highlighted. The process of relations between the Crimean authorities and the Italian colonies on the territory of the Peninsula is also considered. The article covers the issues of the appearance of Italian colonies in the Crimea, the reasons and consequences of the formation of Italian colonies for international trade